Role of radiologist with the advent of artificial intelligence in medical imaging - Boregowdanapalya, Anitha (International Journal of Research in Medical Sciences, 2024)
Artificial intelligence (AI) has rapidly emerged as a transformative tool in healthcare, particularly in radiology, where it offers substantial opportunities to enhance diagnostic precision and workflow efficiency. AI, defined as an artificial entity capable of recognizing patterns, processing data, and executing tasks, has revolutionized traditional imaging practices by automating analyses and reducing subjectivity. While radiologists traditionally rely on expertise and visual assessment to detect and monitor abnormalities, this approach can be limited by variability, fatigue, and bias. AI complements radiologists by providing objective, quantitative assessments, enabling early detection of diseases, lesion classification, and image segmentation with greater speed and accuracy. AI’s integration into radiology workflows supports risk stratification, personalized treatment planning, and predictive analytics, thus enhancing clinical decision-making and patient care. Despite its potential, AI’s current performance remains task-specific, requiring human oversight to ensure accuracy and reliability, especially in ambiguous cases. Challenges such as algorithm bias, ethical considerations, and regulatory hurdles must be addressed to ensure generalizability, transparency, and patient trust. Radiologists play a pivotal role in validating AI tools and advocating for their responsible implementation, ensuring that AI enhances clinical workflows without compromising the essential human connection in healthcare.